PERANCANGAN BUSANA WANITA DEWASA DENGAN MENGGUNAKAN KAIN ULOS SUMATRA UTARA DALAM PAKAIAN READY TO WEAR UNTUK BRAND NATHASIA - Nathasia Mutiara Pascalia; Olivia Gondoputranto (Universitas Ciputra Surabaya, 2016)
This design is made to create a fashion brand for women’s clothing with traditional Ulos fabrics origin from northern Sumatra in ready to wear clothes for brand Nathasia to see that the public is less familiar cultures besides Indonesia Batik textiles. For it made a manufacture this fashion brand with traditional Ulos cloth, is one way to introduce and appreciate Indonesian culture and heritage to the wide community, using designs that always up to date with fashion trends. The design is made based on the results of quantitative research to culture and fashion watchers and lovers of Indonesian culture. Results of research suggest that the culture needs to be preserved and developed for Indonesain culture which are now widely taken and maintained by other nations, then made a brand new design that is expected to change the public perception. All the elements that exist in the process of making this brand, always have an important role to determining the community’s assessment for the product.